Implantação do modelo de melhoria de processo de teste de software brasileiro (mpt.br) - Giotto, Ana Paula (Universidade do Vale do Rio dos Sinos, 2015)
This paper has as main objective to present a project plan for the implantation of the Brazilian software testing process improvement model (MPT.br) in a company inserted in the information technology sector. By focusing on continuous improvement of testing processes to model the implantation of MPT.br seeks to reduce the non-compliance rate in the company's testing process, increase the detection of defects by the system test phase, improve planning, execution and delivery by reduce rework and increase customer satisfaction with the quality of the products deliveries. This paper presents the project management plan with the plans of management integration, scope, time, cost, quality, resources, communications, stakeholders, risk and procurement, necessary for the proper practice of project management and in accordance with the practices addressed in the PMBOK Guide.
Keywords: Plano de gerenciamento do projeto; Modelo de melhoria de processo de teste de software brasileiro; Project management planning; Brazilian software testing process improvement model